Clinical and epidemiological characteristics of older adults with COVID-19 in a southern Santa Catarina city (Research, Society and Development, 2022)
Aims: To characterize the clinical and epidemiological characteristics of older adults infected with COVID-19 during the period from March 2020 to February 2022 in the city of Tubarao, Santa Catarina. Methods: A cross-sectional study was performed with 3919 older adults who had an infection by COVID-19 registered in a database maintained by the Health Foundation of this city. Results: Among this population, the hospitalization rate was 14.8% and the case fatality rate corresponded to 7.7%. Women were more diagnosed with COVID-19 (53.9%), while men were more associated with poor clinical outcomes, accounting for 56.5% of deaths. The most frequent symptom was cough (30.8%), followed by myalgia (22.4%) and headache (20.8%). The most common comorbidity, arterial hypertension, was linked to a higher risk of death. Conclusions: Aging showed its ability to provoke several changes in the response to coronavirus, increasing hospitalization and case fatality rates. The negative effect of the observed comorbidities possibly influenced such results, raising an alert about the need for treatment of chronic diseases and their prevention.